Are privacy concerns still relevant? revisiting consumer behaviour in omnichannel retailing - Cheah, Jun-Hwa; Lim, Xin-Jean; Ting, Hiram; Liu, Yide; Quach, Sara (Elsevier, 2022)
Omnichannel retailing is a new retail norm that focuses on providing a seamless interaction between retailers and consumers. Although the effect of omnichannel retailing on business is increasingly recognised, privacy concerns remain a subject of debate and a delicate issue which could potentially inhibit its growth. Grounded in the Stimulus–Organism–Response (S–O–R) model, the current study investigates consumer behaviour in omnichannel retailing and uses Psychological Reactance Theory (PRT) as the theoretical basis to examine the moderating effect of privacy concerns. A quantitative approach was adopted by means of self-administered questionnaires. 736 consumers were sampled, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings show that consumer perception of channel integration (CPCI), consumer empowerment (CE), and trust significantly affect patronage intention in omnichannel retailing. In addition, when privacy concerns are low, the effects of CPCI and CE on trust are found to be stronger. It underscores the need to synergize channel integration, retailer-consumer relationship empowerment and effective mitigation of privacy concerns in the omnichannel retailing context. Implications of the study are provided.